Multiseptate gallbladder in a child - Mirko Bertozzi; Ilaria Bizzarri; Rossella Angotti; Giulia Fusi; Stefania Ceppi; Giuseppe Di Cara; Susanna Esposito; Mario Messina; Francesco Molinaro (Elsevier, 2019)
Multiseptate gallbladder (MSG) is a rare congenital anomaly. MSG may be accompanied with other abnormalities of the biliary tree. MSG can be asymptomatic and most cases are detected incidentally. Nevertheless, some patients present with biliary pain or colicky abdominal pain due to biliary stasis and calculi. We report a case of MSG in a girl who presented with recurrent abdominal pain and normal laboratory work-up recovered after laparoscopic cholecystectomy. A pediatric literature review of this rare anomaly is also performed. Keywords: Multiseptate gallbladder, Laparoscopic surgery, Children